Hubungan Dukungan Suami dengan Kesiapan Persalinan pada Ibu Hamil Usia Remaja di Sukowono, Jember - lya Farida; Dini Kurniawati; Peni Perdani Juliningrum (Pustaka Kesehatan, 2019)
Childbirth readiness is a birth planning process and anticipation of actions to prevent complications. Teenage pregnant women (<20 years) are at risk because at that age the productive and mental functions are immature. This study aimed to analyze the relationship between husband’s support and childbirth readiness of teenage pregnant women in Sukowono Community Health Center, Jember. The study used correlational approach with cross-sectional study design. Sample size was 34 teenage pregnant women, collected using total sampling. Data was obtained by using questionnaire of husband’s support (validity: 0.759-0.820 and reliability: 0.789) and childbirth readiness (validity: 0.488-0.835 and reliability 0.957). Data analysis used the spearman test. The study showed that the respondents had less husband support, i.e. 19 people and the childbirth readiness was 20 people. The results showed that there was a relationship between husband’s support and childbirth readiness (p value=0,000) and h r=0,623. This study indicated that the higher of husband’s support which receive by pregnant women, the higher of the childbirth readiness. Teenage pregnant women who have good husband’s support will prepare mature labor plan, and further provides safety to mother and fetus.